Implementasi Pemikiran Hermeneutika Martin Heidegger dalam Studi Tafsir Alquran - Supriyanto, Supriyanto (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Implementation of Martin Heidegger's Hermeneutic Thought in the Study of Quranic Interpretation This article examines Martin Heidegger's hermeneutical thinking and its relevance in the discourse on the science of Qur'anic interpretation. This research was designed with qualitative methods and included in library research. The analysis used by the researcher is data reduction, data display, and drawing conclusions. From the study conducted, it can be seen that: 1) Heidegger's metaphysical deconstruction project begins with a realignment of the most basic of metaphysics, namely the question of being; 2) Heidegger is able to include hermeneutics as part of the study of philosophy, precisely as a form of methodical response in which the subject-object perspective must be objectified through a mode of understanding the world above the consciousness of the subject, so as not to produce a rigid and black-and-white understanding of reality-as stated by Wilhem Dilthey with his Geisteswissencheften and Naturwissencheften; 3) Regarding the integration of hermeneutics into the study of the Qur'an, some of Heidegger's thoughts are considered applicable to open horizons regarding the reality of the interpretation of the Qur'an itself. Regarding the facticity or flux experienced by dasein, it gives us an understanding that the socio-cultural conditions in which dasein lives can affect the formation of human understanding (interpreter), which in the study of interpretation is accommodated with the term pre-understanding or mahaula al-mufassir. The theory about the temporality of dasein at least inspires Muslim thinkers to continue to carry out interpretive activities in order to present religious dictums that have relevance to different social conditions between dasein